2013
DOI: 10.1371/journal.pone.0068870
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy Improves Survival In Patients with Severe Hyperparathyroidism: A Comparative Study

Abstract: Background and objectivesSecondary hyperparathyroidism (SHPT) in CKD is associated with an increased risk for mortality, but definitive data showing that parathormone control decreases mortality is still lacking. This study aimed to compare the mortality of patients with severe SHPT submitted to parathyroidectomy(PTX) with those who did not have access to surgery.MethodsThis is a retrospective study in a cohort of 251 CKD patients with severe SHPT who were referred to a CKD-MBD Center for PTX from 2005 until 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 26 publications
1
42
0
8
Order By: Relevance
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A conclusão foi que o cinacalcet não reduz significativamente o risco de manifestação de doença entre tais pacientes, apesar da melhora de parâmetros bioquímicos (26). Entretanto, alguns critérios podem ter alterado os achados, como a não separação dos pacientes por grupo etário ou a alta taxa de PTx no grupo controle, o que pode ter diminuído o número de eventos nesses pacientes (29). Um estudo de custo-efetividade bem conduzido mostrou que a operação é mais custo-efetiva no paciente que tem condições cirúrgicas e que o cinacalcet é superior ao tratamento clínico com análogos do calcitriol em pacientes sem condições cirúrgicas (59).…”
Section: Discussionunclassified
“…Quando a doença não responde mais ao tratamento clínico, indica-se a paratireoidectomia (PTx) (1)(2)(3)11,13,14,(16)(17)(18)(19)(20)23,24,(27)(28)(29)33,34,37,38,40,(42)(43)(44). A PTx pode reduzir significativamente os níveis de fosfato e PTH.…”
unclassified